Growth of hexagonal prism ZnO nanorods on Zn substrates by hydrothermal method and their photoluminescence - Ekthammathat N. (2014)
Hexagonal prism ZnO nanorods were successfully grown on Zn substrates by the 120 °C and 24 h hydrothermal reaction of the solutions with pH of 9-12. Results from XRD, SEM, TEM, SAED and HRTEM showed that the as-synthesized products were wurtzite ZnO with the shape of hexagonal prism nanorods grown along the [0 0 1] direction with smooth prismatic side planes. The PL spectra showed strong emission band at 543 nm in the green-yellow region due to the recombination of electrons trapped in singly ionized oxygen vacancies and photoexcited holes. This facile, reproducible and effective low-cost approach is promising for the future large-scale synthesis of wurtzite ZnO nanostructures for different applications in nanotechnology. © 2012 Elsevier Ltd and Techna Group S.r.l.